2019
DOI: 10.1001/jamaoncol.2019.1870
|View full text |Cite
|
Sign up to set email alerts
|

Disparity of Race Reporting and Representation in Clinical Trials Leading to Cancer Drug Approvals From 2008 to 2018

Abstract: IMPORTANCE Representative racial/ethnic participation in research, especially in clinical trials that establish standards of care, is necessary to minimize disparities in outcomes and to uphold societal equity in health care. OBJECTIVE To evaluate the frequency of race reporting and proportional race representation in trials supporting US Food and Drug Administration (FDA) oncology drug approvals. DESIGN, SETTING, AND PARTICIPANTS Database study of all reported trials supporting FDA oncology drug approvals gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
434
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 424 publications
(456 citation statements)
references
References 26 publications
19
434
3
Order By: Relevance
“…Nonetheless, to our knowledge, this analysis represents the index aggregate utilization of federal public access datasets to assess domestic disparities in racial and ethnic phase 3 clinical trial enrollment. Although others have investigated Food and Drug Administration–approval trials ( 13 ), our use of US-limited, large-scale public access datasets affords a benchmark for future serial assessments and US policy decisions.…”
mentioning
confidence: 99%
“…Nonetheless, to our knowledge, this analysis represents the index aggregate utilization of federal public access datasets to assess domestic disparities in racial and ethnic phase 3 clinical trial enrollment. Although others have investigated Food and Drug Administration–approval trials ( 13 ), our use of US-limited, large-scale public access datasets affords a benchmark for future serial assessments and US policy decisions.…”
mentioning
confidence: 99%
“…Our analysis did reveal a higher accrual of African American patients to non-therapeutic trials at the community sites compared to main campus but did not significantly improve diversity of trial accrual as had been hoped. Loree et al [ 9 ] had reported African Americans and Hispanics representing 3.1% and 6.1% of trial participants respectively, and City of Hope’s rate of African American representation in trial accrual was similarly low. A limitation of our analysis is that our percentages are derived from accrued subjects rather than all subjects; that is to say, the denominator are trial participants, rather than all screened patients or all eligible patients or all patients seen at the clinic, as such data was not available for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline approval and trial characteristics have been reported previously [25]. Of 228 reported trials leading to 204 FDA cancer drug approvals involving 108 different drugs between July 2008 and June 2018, there were 222 trials involving 109,987 patients in which information on sex of participants was available (Table 1).…”
Section: Female/male Enrollment Across All Trialsmentioning
confidence: 99%